Sectoral Studies on Decent Work in Global Supply Chains : Comparative analysis of opportunities and challenges for social and economic upgrading. - ILO (ILO, 2016)
This publication analyses economic and social upgrading in global supply chains in four different sectors of the economy: animation/visual effects (VFX), electronics, gold and retail. These four sectors were selected for their diversity to provide insight into general trends across the global economy. A comparison of the four sectors aids understanding the social and the economic implications of supply chains within the context of the changing global economy and helps identify potential areas for future work.